2020
DOI: 10.1136/sextrans-2019-054216
|View full text |Cite
|
Sign up to set email alerts
|

Sexually transmitted infections in persons living with HIV infection and estimated HIV transmission risk: trends over time from the DC Cohort

Abstract: ObjectiveA rise in incidence of STIs has been noted in the USA and in the District of Columbia (DC). We aim to describe changes in incident STIs among persons in care for HIV in Washington, DC as well as trends in HIV viral load among those with incident STIs.MethodsWe conducted a retrospective DC Cohort analysis (n=7810) measuring STI incidence (syphilis, gonorrhoea and chlamydia) as well as incare viral load (ICVL) and percentage with all viral loads less than the limit of detection (%<LLOD) by year (2012… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 11 publications
3
14
0
Order By: Relevance
“…A history of STIs was the second factor most strongly associated with monoinfection or coinfection, with a prevalence of reported cases of syphilis and gonorrhea, respectively. Recent studies have shown that the highest risk for STIs is observed in young MSM from the most vulnerable socioeconomic groups 50 , 62 ; among these, those diagnosed with syphilis and gonorrhea have the highest rate of HIV coinfection 102 , similar to our findings. These data are particularly worrying for Brazil because the incidence rates of acquired syphilis have been increasing since 2010 103 , and there is an estimated global increase in cases of gonorrhea, especially in MSM in developing countries 104 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…A history of STIs was the second factor most strongly associated with monoinfection or coinfection, with a prevalence of reported cases of syphilis and gonorrhea, respectively. Recent studies have shown that the highest risk for STIs is observed in young MSM from the most vulnerable socioeconomic groups 50 , 62 ; among these, those diagnosed with syphilis and gonorrhea have the highest rate of HIV coinfection 102 , similar to our findings. These data are particularly worrying for Brazil because the incidence rates of acquired syphilis have been increasing since 2010 103 , and there is an estimated global increase in cases of gonorrhea, especially in MSM in developing countries 104 .…”
Section: Discussionsupporting
confidence: 90%
“…Although the number of new HIV cases identified is stable nationally, especially in the northern region of the country 47 , 48 , our data warn of an increase in coinfections in PLHIV, a predisposition observed in Brazil 49 and internationally 50 , especially among young men.…”
Section: Discussionmentioning
confidence: 62%
“…Almost 70% of GC infections were at rectal, pharyngeal, or concurrent rectal and pharyngeal sites, and >50% of CT infections were at the rectal site only. Consistent with prior studies, younger PWH experienced greater rates of GC/CT at each anatomic site, while TW/MSM experienced greater rates of extragenital GC/CT [ 3 , 5 , 6 , 33 ]. Black PWH were more likely to experience urogenital CT infections compared with White PWH.…”
Section: Discussionsupporting
confidence: 85%
“…To achieve the new goals of “DC Ends HIV” in the District of Columbia, enhanced and timely prevention, rapid testing, and partner treatment for HIV and STIs are necessary [ 8 ]. Previously, we described significant yearly increases in STI incidence rates observed across all adult age groups in the DC Cohort [ 12 , 23 ]. Identifying geographically specific information regarding STIs and potential for HIV transmission allows for expansion of resources on treatment and prevention of HIV, including outreach for U = U, PrEP, and STI prevention campaigns.…”
Section: Discussionmentioning
confidence: 99%